PENEGAKAN HUKUM BISNIS DITINJAU DARI UNDANG-UNDANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT (Lex Jurnalica, 2019)
In business law there are several activities carried out by business people, including trade, industry or services. The actors in business activities tend to compete to increase profits. In unknown business law about unfair competition such as monopoly, oligopoly or monopsony. This is prohibited in law. For law enforcement in business competition, it is necessary to have a body that oversees the business activities. Based on Law Number 5 Year 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, it has been regulated regarding the prohibition of monopolistic practices and unfair business competition. The importance of the role of the Business Competition Supervisory Commission in business law enforcement must be followed up by both the government and the actors in business activities.